Mechanism of miR-30b-5p-Loaded PEG-PLGA Nanoparticles for Targeted Treatment of Heart Failure - Yu Ren; Xiao Wang; Hongyu Liang; Wenshuai He; Xingsheng Zhao (Frontiers Media S.A., 2021)
Objective: Exploring the effectiveness of miR-30b-5p-loaded PEG-PLGA nanoparticles (NPs) for the treatment of heart failure and the underlying mechanism.Methods: PEG-PLGA characteristics with different loading amounts were first examined to determine the loading, encapsulation, and release of miR-30b-5p from NPs. The effects of miR-30b-5p NPs on cardiac function and structure were assessed by immunofluorescence, echocardiography, HE/Masson staining, and TUNEL staining. The effects of NPs on the expression of factors related to cardiac hypertrophy and inflammation were examined by RT-PCR and western blotting, and the mechanism of miR-30b-5p treatment on heart failure was explored by dual luciferase reporter assay and RT-PCR.Results: The size of PEG-PLGA NPs with different loading amounts ranged from 200 to 300 nm, and the zeta potential of PEG-PLGA NPs was negative. The mean entrapment efficiency of the NPs for miR-30b-5p was high (81.8 ± 2.1%), and the release rate reached 5 days with more than 90% release. Distribution experiments showed that NPs were mainly distributed in the heart and had a protective effect on myocardial injury and cardiac function. Compared with a rat model of cardiac failure and miR-30b-5p-non-loaede NP groups, the expression of cardiac hypertrophy markers (ANP, BNPβ-MHC) and inflammatory factors (IL-1β, IL-6) were significantly decreased. Dual luciferase reporter assay assays indicated that miR-30b-5p exerted its effects mainly by targeting TGFBR2.Conclusion: PEG-PLGA NPs loaded with miR-30b-5p improved cardiac function, attenuated myocardial injury, and regulated the expression of factors associated with cardiac hypertrophy and inflammation by targeting TGFBR2.